Frequency of use of household products containing VOCs and indoor atmospheric concentrations in homes. Issue 5 (15th April 2021) - Heeley-Hill, Aiden C.; Grange, Stuart K.; Ward, Martyn W.; Lewis, Alastair C.; Owen, Neil; Jordan, Caroline; Hodgson, Gemma; Adamson, Greg
Abstract : VOCs are used ubiquitously in consumer products. This population study investigates a wide-range of VOC concentrations indoors and links high butane concentrations with universal and frequent aerosol use. Abstract : Volatile organic compounds (VOCs) are a key class of atmospheric emission released from highly complex petrochemical, transport and solvent sources both outdoors and indoors. This study established the concentrations and speciation of VOCs in 60 homes (204 individuals, 360 × 72 h samples, 40 species) in summer and winter, along with outdoor controls. Self-reported daily statistics were collected in each home on the use of cleaning, household and personal care products, all of which are known to release VOCs. Frequency of product use varied widely: deodorants: 2.9 uses home per day; sealant-mastics 0.02 uses home per day. The total concentration of VOCs indoors (range C2 –C10 ) was highly variable between homes e.g. range 16.6–8150 μg m −3 in winter. Indoor concentrations of VOCs exceeded outdoor for 84% of households studied in summer and 100% of homes in winter. The most abundant VOCs found indoors in this study were n -butane (wintertime range: 1.5–4630 μg m −3 ), likely released as aerosol propellant, ethanol, acetone and propane. The cumulative use VOC-containing products over multiday timescales by occupants provided little predictive power to infer 72 hour averaged indoor concentrations. However, there was weak covariance between the cumulative usage of certain products and individual VOCs. From a domestic emissions perspective, reducing the use of hydrocarbon-based aerosol propellants indoors would likely have the largest impact.